2019
DOI: 10.4103/jlp.jlp_59_19
|View full text |Cite
|
Sign up to set email alerts
|

Co occurrence of two 16S rRNA methyltrasferases along with NDM and OXA 48 like carbapenamases on a single plasmid in Klebsiella pneumoniae

Abstract: BACKGROUND: The carbapenemase-encoding genes, bla NDM- and bla OXA-48 - like , confer resistance to all the known beta-lactams and are encountered along with other beta-lactamase-encoding genes and/or 16S ribosomal RNA (rRNA)-methylating genes. The co-occurrence of bla NDM and bla OXA-48 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Such a frequent association between carbapenemase-producing and RMTase-producing Enterobacterales was already reported in different parts of the world [5][6][7][8][9][10][11][12][13]21,[27][28][29][30][31][32][33][34][35][36][37]. The origin of those isolates being identified in Switzerland could be autochthonous theoretically; nevertheless, clinical information (only partially obtained and therefore not presented in that study) showed that many of them corresponded to imported cases, and particularly from Eastern European countries, from Italy, and from the Indian subcontinent.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Such a frequent association between carbapenemase-producing and RMTase-producing Enterobacterales was already reported in different parts of the world [5][6][7][8][9][10][11][12][13]21,[27][28][29][30][31][32][33][34][35][36][37]. The origin of those isolates being identified in Switzerland could be autochthonous theoretically; nevertheless, clinical information (only partially obtained and therefore not presented in that study) showed that many of them corresponded to imported cases, and particularly from Eastern European countries, from Italy, and from the Indian subcontinent.…”
Section: Discussionmentioning
confidence: 72%
“…The armA gene was mostly carried by an IncA/C-type plasmid ( n = 9), except for a single isolate carrying an armA -positive IncR plasmid ( n = 1). Two isolates, namely a single K. pneumoniae and a single E. coli isolate, recovered from the same patient, carried both the bla OXA-181 and armA genes on a single IncA/C-type plasmid [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Seven sets of uniplex PCRs were performed for 16SrRNA methyltransferase using primers established in our earlier study. 15 Each reaction volume contained 2 µL of the deoxyribonucleic acid (DNA) template added to the master mix which includes 10 pmol of the forward and reverse primers (Sigma-Aldrich), 10 mm deoxyribonucleotide triphosphate (Takara), 5U Taq polymerase (Takara), and 10× buffer with MgCl 2 (Takara).…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%
“…It seems that the presence of carbapenem resistance genes on conjugative plasmids could lead to their worldwide dissemination and therefore the high prevalence of CPK isolates could be a serious problem for the health care system all over the world. Also, the coexistence of carbapenemase-encoding genes with other resistance genes such as aminoglycoside-modifying genes in K. pneumoniae isolates exacerbates the problem of antibiotic resistance as a challenge in the curing of infectious [9,10]. The harboring of these resistance genes on mobile genetic elements (MGEs), including class 1 integron, transposons, and insertion sequences are usually carried on conjugative plasmids, contribute to expansion of antimicrobial resistance (AMR).…”
Section: Introductionmentioning
confidence: 99%